SITUASI DAN KONDISI ARAB DI MASA JAHILIYAH - Shofil Fikri; Agung Izul Haq (Tarbawi, 2023)
The Arab nation before the teachings brought by the Prophet Muhammad SAW became a nation known as the Jahiliyyah nation, a bad nation and they did many things, such as gambling, killing girls on a spree and so on. However, there has also been economic progress due to its precise geographical location which has become a trade route from city to city. The Arab nation has 2 groups, namely Qathaniyun and Adnaniyun. There are also characteristics of the political system that existed during the Jahiliyah era, such as tribal division, oligarchic leadership, and polytheism. At that time they already had quite a lot of beliefs, such as Judaism, Christianity, the al Hunafa' group, the Mulhad group, and magi beliefs. Their culture is also very diverse, but from some of these cultures there is one thing that is more inclined, namely poetry, there they glorify poets so much that they often hold competitions for several poets and hold orgies afterward. Here the methodology I use is qualitative methodology, a method that I took from several articles that I researched and explained in my writing. And as a result, the Arabian Peninsula became a popular nation and could be said to provide benefits to better understand the situation of Arabia in the pre-Islamic era.